Characterization of Patients with Cystic Fibrosis in Multidisciplinary Consultation - Caridad Llull Tombo; Mercedes Fonseca Hernández; Ileana García Rodríguez; Juan Carlos Yanes Macías; Daymí Tió González; Yoandra León Rayas (Universidad de las Ciencias Médicas de Cienfuegos, 2020)
Foundation: cystic fibrosis is a multisystemic inherited disorder in children and adults, characterized by obstruction and infection in the respiratory tract and by symptoms and signs of the digestive system with its consequences. Objective: to characterize patients with cystic fibrosis in the province of Cienfuegos. Methods: an observational, descriptive and cross-sectional study was carried out at the Paquito González Cueto de Cienfuegos University Pediatric Hospital in the cystic fibrosis consultation, from January 1 to December 31, 2018. Patients were group according to the following variables: age, sex and municipality of origin, the clinical manifestations that suggested the diagnosis, age of presentation and the age at diagnosis, presence of digestive manifestations, germs isolated in microbiological studies, mutations found in patients with cystic fibrosis. For the processing of numerical data descriptive statistics techniques were used. Results: a greater number of patients with more than 18 years (33 %) was observed, 8 patients (66.6 %) and the mestizos predominated with 66.6 %. The largest number of patients was from Cienfuegos 4 municipality (33.3 %). It was observed that in 8 of the patients the first symptoms appeared in the first year of life. Regarding clinical manifestations, pancreatic insufficiency was present in all the patients. Psedomonaaeruginosa was isolated. Conclusions: cystic fibrosis in Cienfuegos behaves as a disease similarly to the rest of the world with clinical-epidemiological characteristics such as: onset of pathology, predominant sex, onset of the disease, main clinical manifestations and the most frequent isolated germs.